Microsoft office visio professional 2003 - Seppanen, Marvin S. (McGraw-Hill/Irwin, 2005)
This books describes and illustrates how to create an integrated business process analysis and improvement system using popular software tools such as Excell, Vision, Arena, anf Visual Basic for Application to create an integrated business process analysis and redesign capability. (mhhe.com)